Analisis Strategi Penyaluran Dana Zakat Infaq Sedekah Untuk Mensejahterahkan Masyarakat Pada Rumah Yatim Medan - Lubis, Dian Ariska; Amsari, Syahrul (Universitas Labuhanbatu, 2024)
The purpose of this study is to find out the strategy carried out by the Medan Orphan House in channeling zakat infaq alms funds. The author found several problems that occurred when distributing zakat infaq alms funds, namely the uneven distribution of zakat infaq alms funds where distribution was only given to those who really needed it, but there were people who cheated so they could get help. The author uses the field observation method in his research by using interviews and documentation. The results in this study indicate that implementing the strategy is the key to success in channeling ZIS funds. The strategy implemented by Laznas Rumah Yatim in channeling ZIS funds for the welfare of the community includes distribution targets, distribution objects, planning for zakat distribution and methods for distributing zakat. The results of the study show that the Medan Orphanage has succeeded in distributing zakat, infaq, alms funds to mustahik in need.